PERANAN MATAKULIAH PENDIDIKAN JASMANI DI PERGURUAN TINGGI - Sukadiyanto Sukadiyanto (LPMPP Universitas Negeri Yogyakarta, 2008)
AbstractHigher education students world reflects a life emphasizing academic morals.Unfortunately, there have been a lot of student fights triggered by trivial matters.This indicates a crisis in academic morals and stains campuses as centers foracademic life. If students as the intellectual young generation were continuouslyinvolved the culture of fight, the nation would be in danger. Therefore, it isnecessary to find a solution that can make use of students excessive energy todevelop their creative potentials and imaginations through academic activities tomake them mature and skillful. It is the responsibility of a higher educationinstitution to develop students potentials so that they can give positivecontributions to society through their activities. The Yogyakarta State Universityhas made a breakthrough by including Physical Education (PE) in the 2009Curriculum. It is an initial step to equip students with both hard skills and softskills. PE makes use of physical activities in an attempt to attain educational goals.PE provides students with essential values that they can utilize in their campus andsocial life. In this way, students will possess mental toughness necessary to live thecompetitive life at present.Keywords: Physical Education, essential values